Pemanfaatan Media Geschool Dalam Pembelajaran Pendidikan Agama Islam - Atikah, Septina; Wiza, Rahmi (An-Nuha, 2023)
The background of this research is that researchers want to know the benefits of Geschool media in learning PAI (Islamic Religious Education). The purpose of this study was to find out how the use of Geschool l media in learning Islamic religious education at SMP Negeri 7 Padang, to find out how teachers and students perceive the use of Geschool media in learning Islamic religious education at SMP Negeri 7 Padang, to find out the supporting and inhibiting factors in using Geschool media in learning Islamic religious education at SMP Negeri 7 Padang. The research method used is qualitative, using case studies. Data was obtained through interviews, observation, and documentation. Data analysis through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the discussion found by researchers after conducting field research, it can be concluded that SMPN 7 Padang has maximized the use of Geschool as a student learning medium both in a fully online system and also in blended learning (online and offline).